PENGETAHUAN DAN SIKAP SISWA DENGAN TINDAKAN PENCEGAHAN COVID-19 - Sigalingging, Ganda; Ginting, Magdalena; Nasution, Zulkarnain; Tarigan, Fatmawati (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Background: The world was shocked by the emergence of COVID-19 virus infection. Therefore itis necessary to apply new habits such as washing hands, wearing masks, maintaining distance, avoiding crowds, and limiting mobility. Purpouse: The aim to analyze the relationship knowledge and attitudes of students the prevention of COVID-19 at state elementary school 030349 parfruits, Dairi regency.Method: This analytical survey study applied cross sectional approach. Seventy people were involved as the population in this study. this study used total sampling wherein the number of sample equals to the number population. in analyzing the data, chi-square test with ?<0.05. Results: The results showed that there was a relationship of knowledge and preventive measures for COVID-19 with pvalue of 0.02. There is a relationship attitudes and precautions for COVID-19 with pvalue of 0.02. Conclusion: The conclusion there was a relationship knowledge and attitudes with prevention of COVID-19. Advice: To the school to provide understanding to implement health protocols. Facilitating students by providing handwashing with soap (CTPS) facilities with running water and hand sanitizers in every class, teacher's room, school gate and other places students often access. Educating students to do CTPS and correct coughing/sneezing ethics, in collaboration with the puskesmas.